8=6v

Rewrite the equation as 6v=8.

6v=8

Multiply each term by v and simplify.

Multiply each term in 6v=8 by v.

6v⋅v=8⋅v

Cancel the common factor of v.

Cancel the common factor.

6v⋅v=8⋅v

Rewrite the expression.

6=8⋅v

6=8v

6=8v

Rewrite the equation as 8v=6.

8v=6

Divide each term by 8 and simplify.

Divide each term in 8v=6 by 8.

8v8=68

Cancel the common factor of 8.

Cancel the common factor.

8v8=68

Divide v by 1.

v=68

v=68

Cancel the common factor of 6 and 8.

Factor 2 out of 6.

v=2(3)8

Cancel the common factors.

Factor 2 out of 8.

v=2⋅32⋅4

Cancel the common factor.

v=2⋅32⋅4

Rewrite the expression.

v=34

v=34

v=34

v=34

v=34

The result can be shown in multiple forms.

Exact Form:

v=34

Decimal Form:

v=0.75

Solve for v 8=6/v